SOCIAL JUSTICE FOR MINERS AND MINING-AFFECTED COMMUNITIES: THE PRESENT AND THE FUTURE - Raashi Chauhan (Obiter, 2018)
South Africa’s history of discriminatory and unfair apartheid laws resulted in significant hardship and suffering of miners and mining communities. Post-apartheid brought about a number of legislative reforms in an attempt to right the wrongs of the past. More than twenty years later, many mining-affected communities and areas are still exposed to water, soil, noise and dust pollution. This not only causes ill health but also causes social disruption, increased crime and forced resettlement. South Africa has all the necessary environmental legislation in place yet communities continue to suffer from the harmful effects of mining. Very often, the poorest and most vulnerable communities suffer the worst of these consequences. Due to poor enforcement and management by governmental departments, there remains inadequate compliance with these laws within the mining sector. It is important to consider what mining companies have done to rehabilitate the environment and the communities around them. The article concludes with suggestions on how environmental and mining law can play a better role in enhancing the lives of mining communities.